Thermodynamic optimization and phase equilibria study of the MgO–ZnO, CaO–ZnO, and CaO–MgO–ZnO systems. Issue 8 (15th April 2023) - Jeon, Junmo; Lindberg, Daniel
Abstract: The binary MgO–ZnO and CaO–ZnO systems and the ternary CaO–MgO–ZnO system were thermodynamically optimized with phase equilibria studies in this study. Bragg-Williams random mixing model was used for solid solutions, while Modified Quasichemical Model was used for liquid solution. The thermodynamic optimization was conducted using Factsage 8.1 thermochemical software. The optimized phase diagrams fit well with phase equilibria experimental results. The phase equilibria studies were performed for the MgO–ZnO systems at 600 °C, 650 °C, 700 °C, and 1000 °C, and for CaO–MgO–ZnO systems at 1500 °C, 1550 °C, and 1600 °C. Quenched samples were analyzed by SEM/EDS to confirm equilibrium phases. Liquid phases were newly observed in the CaO–MgO–ZnO systems at 1550 °C and 1600 °C.